Glycerol hydro-deoxygenation aided by in situ H2 generation via methanol aqueous phase reforming over a Cu–ZnO–Al2O3 catalyst. Issue 14 (5th April 2016) - Yfanti, V.-L.; Vasiliadou, E. S.; Lemonidou, A. A.
Abstract : Methanol APR–glycerol HDO reactions were successfully coupled to produce 1, 2-propanediol at high yields over an efficient CuZnAl catalyst. Abstract : A tandem catalytic cycle of methanol aqueous phase reforming–glycerol hydro-deoxygenation targeted to 1, 2-propanediol formation under inert conditions is investigated. The H2 needed for glycerol hydro-deoxygenation is provided in situ via methanol reforming. The effects of reaction time, temperature, methanol concentration and system pressure were investigated over a Cu : Zn : Al bulk catalyst. The catalytic results showed that 1, 2-propanediol selectivity and yield depend on reaction temperature and reaction time combination. Higher methanol concentrations favor glycerol hydro-deoxygenation towards the desired pathway, resulting in a significant increase in 1, 2-propanediol selectivity. Under optimum reaction conditions ( t = 1 h, T = 250 °C, 36 v/v% C MeOH + 9 v/v% C GLY, 1.0 < P N2 < 3.5 MPa), glycerol was almost fully converted (95.9%), with 79.4% selectivity (76.2% maximum yield) to 1, 2-propanediol. Upon catalyst reuse, the Cu : Zn : Al catalyst showed satisfactory stability. An initial loss of activity (35.8%) was observed, which was ascribed to Cu agglomeration; however, catalyst performance was improved and stabilized after the third run, possibly due to Cu re-dispersion. It is proposed that metallic Cu 0 efficiently catalyzes glycerol hydro-deoxygenation, while methanol reforming is mainly catalyzed by metallic Cu 0 and facilitated by the interaction of Cu 0 with ZnO–Al2 O3 structures.